Fishing to farming livelihood diversification: Perceptions from commercial fishers and shellfish farmers in the United States - Hayley R. Lemoine; Adriane K. Michaelis; Sarah E. Lester (People and Nature)
Abstract Aquaculture, or the farming of aquatic species, is a rapidly growing, multi‐billion‐dollar sector of the U.S. food industry. At the same time, many wild capture fisheries are contending with financial, social or ecological challenges that threaten fishers' abilities to maintain their livelihoods, leading to suggestions that fishers could diversify or transition into aquaculture. However, research looking at commercial fishing to seafood farming livelihood diversification or transitions in the United States is extremely limited. We examined how commercial fishers and shellfish farmers in Maine, New York and Florida perceive the shift (diversification or transition) from commercial fishing to shellfish aquaculture as part of their livelihood strategy. We used reflexive thematic analysis to analyse the data we collected from 66 semi‐structured interviews with commercial fishers, shellfish farmers and fisher‐farmers. We found that fishers are perceived as having valuable skills on the water and experience in the seafood industry that non‐fishers often lack and could make them well suited to seafood farming. Alternatively, non‐fishers are equipped with other valuable skills and experience that fishers often lack, such as business management, marketing, site mapping and design, or even comfort staying in one spot for long periods of time. Overall, transitioning or diversifying from commercial fishing to shellfish farming was not seen as a more logical alternative livelihood strategy for fishers than for non‐fishing professionals. The suitability of aquaculture for fishers was perceived to be most influenced by sociocultural factors (e.g. personal networks) and psychological attributes (e.g. ‘grittiness’). Policy implications. As aquaculture investment and expansion in the United States continue to increase, our research suggests that policies or programmes intended to facilitate livelihood diversification or transitions into shellfish aquaculture should consider targeting groups beyond just fishers, and account for the ways that local social and cultural factors influence seafood‐based livelihood strategies. Read the free Plain Language Summary for this article on the Journal blog.